2021
DOI: 10.1002/hbm.25619
|View full text |Cite
|
Sign up to set email alerts
|

Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency

Abstract: Repetitive TMS (rTMS) with a frequency of 5–10 Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right‐handed, healthy subjects (m = 8, median age: 29 yrs) were investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The current results confirmed that both high and low TMS frequencies could affect healthy participants’ language performance, with high frequencies exerting more stable effects. This accords with a series of studies focusing on the influence of specific stimulation parameters (including frequency) on TMS effects ( Sparing et al, 2001 ; Sollmann et al, 2015 , 2018 ; Nettekoven et al, 2021 ), which support the idea that higher frequencies may induce more reliable disruption of language functions. There are two possible explanations for this finding.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The current results confirmed that both high and low TMS frequencies could affect healthy participants’ language performance, with high frequencies exerting more stable effects. This accords with a series of studies focusing on the influence of specific stimulation parameters (including frequency) on TMS effects ( Sparing et al, 2001 ; Sollmann et al, 2015 , 2018 ; Nettekoven et al, 2021 ), which support the idea that higher frequencies may induce more reliable disruption of language functions. There are two possible explanations for this finding.…”
Section: Discussionsupporting
confidence: 88%
“…The distraction caused by physical discomfort (e.g., twitching and contractions of face muscles) or more severe side effects (e.g., dysarthria resulting from stimulation-induced contraction of cranial muscles, Sollmann et al, 2018 ) are non-specific TMS effects and are very likely to confound the interpretation of the results. Therefore, it has been proposed that higher frequencies correlated with lower pain levels and were therefore more optimal for obtaining reliable TMS effects ( Nettekoven et al, 2021 ). Secondly, it is likely that using TMS frequencies matching with the natural frequency band of endogenous brain oscillations increases the probability of TMS pulses to interfere with cortical processing at the appropriate timing ( Thut and Miniussi, 2009 ; Miniussi et al, 2013 ; Nettekoven et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure was designed to induce a stimulation-related interference either during the encoding phase (early TMS) or on the retention phase (late rTMS) of the memory items, respectively. A rapid sequence of pulses at 30 Hz has been shown to improve the efficacy and reliability of the interference effects of TMS compared to lower stimulation frequencies [ 60 ]. rTMS trials were interleaved by trials with no stimulation (i.e., No-TMS trials).…”
Section: Methodsmentioning
confidence: 99%